Odpowiedź :
Odpowiedź:
c)
11 13/17 -
2 15/17 =
8 15/17
d)
3 1/4 -
2 3/4 =
5/4 - 3/4 =
=== 2/4
e)
15 1/3 -
13 2/3 =
7/3 - 2/3 = 5/3
=
1 2/3
f)
5 4/11 -
2 9/11 =
37/11 - 9/11 =
28/11
[tex]c) \ 11\frac{13}{17}-2\frac{15}{17} = 10\frac{30}{17}-2\frac{15}{17} = 8\frac{15}{17}\\\\d) \ 3\frac{1}{4}-2\frac{3}{4} = 2\frac{5}{4}-2\frac{3}{4} = \frac{2}{4} = \frac{1}{2}\\\\e) \ 15\frac{1}{3}-13\frac{2}{3} = 14\frac{4}{3}-13\frac{2}{3} = 1\frac{2}{3}\\\\f) \ 5\frac{4}{11} - 2\frac{9}{11} = 4\frac{15}{11}-2\frac{9}{11} = 2\frac{6}{11}[/tex]